Analisis Kapabilitas Organisasi dan Lingkungan Usaha Terhadap Kinerja Bisnis dan Implikasinya bagi Pengembangan Usaha di Pasar Tradisional Spesifik PD Pasar Jaya - Suharyono Suharyono; Musa Hubeis; Setiadi Djohar; Hartoyo Hartoyo (School of Business, Bogor Agricultural University (SB-IPB), 2010)
Small and Medium Enterprises (SMEs) and traditional market occupies the largest proportion of the industrial sector and plays an important role in economic development, improvement of social welfare and employment in many countries, especially developing countries (including Indonesia). Based on Structural Equation Modeling (SEM) analysis has found dimensions and the dominant factors that affect real, both as a stimulus (incentive) as well as obstacles in improving business performance from the aspect of profit. Dimensions of the internal corporate environment, particularly organizational resource factors as stimulus organization, increase business performance, while factors on company's external environment dimensions none of which have real impact on business performance. Based on Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis, it is proposed several business development strategies that will productive if implemented simultaneously. These strategies include maintain market share, market expansion and optimize production capacity/sales (S – O Strategies); improve the professionalism of business management, reduce cost, technical development and work systems development (W – O Strategies); improve competitiveness, technology development and range of products merchandises development (S – T Strategies); human resources development, financial management, and partnership networking development (W – T Strategies).